American Journal of Preventive Cardiology: Area Deprivation Index and Oral Anticoagulation in New Onset Atrial Fibrillation - Toluwa D. Omole; Jianuhi Zhu; William Garrard; Floyd W. Thoma; Suresh Mulukutla; Annie McDermott; Brandon M. Herbert; Utibe R. Essien; Jared W. Magnani (American Journal of Preventive Cardiology, 2022)
Objective: Oral anticoagulation is a standard of care for thromboembolic stroke prevention in individuals with atrial fibrillation (AF). Social determinants of health have had limited investigation in AF and particularly in access to anticoagulation. We examined the relation between area deprivation index (ADI) and anticoagulation in individuals at risk of stroke due to AF. Methods: We conducted a retrospective analysis of patients with incident, non-valvular AF from 2015-2020 receiving care at a large, regional health center. We extracted demographics, medications, and problem lists and used administrative coding to identify comorbid conditions and relevant covariates, and individual-level residential address to ascertain ADI. We examined the relation between ADI and receipt of prescribed oral anticoagulation (warfarin or direct-acting oral anticoagulant, or DOAC) at 90 days following AF diagnosis in multivariable-adjusted models. Results: Following exclusions, the dataset included 20,210 individuals (age 74.5±10.9 years; 51% women; 94% white race). In multivariable-adjusted analyses, individuals in the highest quartile of ADI had a 16% lower likelihood of receiving anticoagulation prescription than those in the lowest ADI quartile (Odds Ratio [OR] 0.84; 95% Confidence Interval [CI], 0.75-0.95) at 90 days following AF diagnosis. In those receiving anticoagulation, individuals in the highest ADI quartile had a 24% lower likelihood of receiving a DOAC prescription as opposed to warfarin prescription than those in the lowest quartile (OR 0.76; 95% CI, 0.60-0.96) at 90 days following AF diagnosis. Conclusions: We demonstrate the association of higher neighborhood deprivation as determined by ADI with decreased likelihood of (1) anticoagulation prescribing for stroke prevention in AF and (2) prescription of a DOAC when any oral anticoagulation is prescribed. Our results suggest neighborhood-based health inequities in the receipt of anticoagulation prescription for stroke prevention in AF in a large, regional health care system.